“Parish Revolution” of 1917 in Nizhny Novgorod Diocese - N. E. Arkhipova (Научный диалог)
The manifestations of the “church revolution” at the parish level in the Nizhny Novgorod diocese in the spring and summer of 1917 are considered. The novelty of the study lies in the research of the “parish revolution” at the local level based on the analysis of unpublished documents of the Nizhny Novgorod Spiritual Consistory, the provincial commissioner, etc., introduced into scientific circulation for the first time. The author singled out the following manifestations of the “revolution” in the Nizhny Novgorod parishes: the unauthorized setting of prices by the peasants for the fulfillment of the requirements, the refusal to pay diocesan taxes, the robbery of church cash desks, the protests of parishioners against some priests, the arrests, robberies and expulsions of objectionable pastors, conflicts between the higher and lower clergy, the seizure peasants of church lands. The author comes to the conclusion that the cases in which priests became victims of arbitrariness, nevertheless, were not widespread in the diocese. It is shown that the diocesan and local secular authorities could not cope with the manifestations of the “parish revolution”. It is concluded that the “parochial revolution” caused some material damage to the diocese, aggravated the financial situation of some of the clergy, undermined the authority of the spiritual authorities, and increased the contradictions between the higher and lower clergy.